Whitney Biennial 2010. - Weinberg, Adam; Bonami, Francesco; Carrion-Murayari, Gary; Whithney Biennial New York City 2010 (New Haven : Yale University Press, 2010)
Adamo, David ; Aldrich, Richard ; Asher, Michael ; Auerbach, Tauba ; Berman, Nina ; Bhabha, Huma ; Brand, Josh ; Casebere, James ; Clements, Dawn ; Condo, George ; et al.
Whitney Biennial 2010, Whitney Museum of American Art, New York, 25.02 - 30.05.2010
kunstcatalogus